Teaching and learning using 21st century educational technology in accounting education: Evidence and conceptualisation of usage behaviour - Mat Dangi, Mohamad Ridhuan (Australasian Society for Computers in Learning in Tertiary Education (ASCILITE), 2023)
Technologies are ubiquitous in the 21st century, and educators need to integrate relevant technologies into their teaching practices to meet stakeholders’ expectations and keep abreast with the accounting profession’s advancement. A mixed-method approach of quantitative and qualitative techniques was used in this study, with the latest version of the SPSS software (version 26) and NVivo software to analyse the data. The results depict the accounting educators’ usage efforts of 21st century educational technology tools and platforms, it is neither highly prevalent nor optimised. Future researchers could expand the investigation of 21st century educational technology by utilising the proposed constructs, model and hypotheses from this study’s qualitative findings. The study revives the stagnant educational technology literature in accounting education and explicates technology usage issues in accounting education, specifically in developing countries and the Asian region. Implications for practice or policy: • Education ministries, higher education institutions, faculties, policymakers and academics should encourage educators to adopt and integrate 21st century educational technology into their practices. • The integration of 21st century educational technology in teaching and learning practice should align with individual attributes, technology characteristics and organisational factors. • Accounting educators must acquire technological competence through appropriate professional development and training programmes.